Lateral third clavicle fracture with concomitant glenoid and acromian fractures: A rare injury pattern - KC, Kapil Mani; GC, R; Acharya, S (Nepal Orthopaedic Association Journal, 2021)
Combination of lateral third clavicle fracture (Neer type II), Ideberg type III glenoid fracuture and acromian fracture is very rare fracture pattern. High index of suspicion after careful clinical and radiological examination is mandatory; otherwise glenoid fractures can be missed and functional outcomes will significantly be altered. This type of fracture pattern requires timely diagnosis, proper planning and proper use of implants. We report a 39 years old female patient with Neer type II lateral third clavicle fracture with concomitant Ideberg type III glenoid fracture and undisplaced acromian fracture visualized only in CT scan which was diagnosed and managed successfully with single incision on lateral aspect of clavicle and fixed with trans-acromian Kirschner wire for clavicle fracture and cannulated screw for glenoid fracture after indirect reduction of fracture.